How does sugar-sweetened beverage consumption relate to sleep and mental health in adolescents? A scoping review - Di Nucci, Annalisa; Cardamone, Erica; Rossi, Laura; Silano, Marco (Frontiers in Nutrition, 2026)
IntroductionOver the last years, adolescents have exhibited high consumption of sugar-sweetened beverages (SSBs). During this developmental stage, characterized by profound biological and psychosocial changes, individuals are more susceptible to sleep disturbances, as well as psychological, behavioral, and emotional difficulties. The present scoping review aims to offer insights into how SSBs consumption relates to sleep and mental health outcomes in adolescents.MethodsA systematic search and selection process was conducted across four electronic databases. Studies, published in peer-reviewed international scientific journals up to April 2025, in English, and examining the relation between SSBs, sleep, and mental health in adolescents were considered eligible.ResultsThe search identified 288 references after duplicate removal. Based on PCC framework, 57 studies were included. Slightly fewer studies investigated the association between SSBs consumption and sleep outcomes (n = 25), compared with those focusing on mental health outcomes (n = 32). Evidence suggests a potential link between SSBs consumption, sleep, and mental health, indicating that higher intake may be associated with increased sleep disturbances and mental health problems.DiscussionOverall, the results of this review advance the hypothesis of a possible bidirectional relationship between SSBs consumption and both adverse sleep and mental health outcomes. These findings should be interpreted with caution, due to the main gaps identified. The current evidence calls for future studies that use interventional and longitudinal designs, focus on adolescence, target regions with rising SSBs consumption and sleep or mental health issues, analyze SSBs subgroups separately, and address all sleep dimensions. This review also highlights the need for tailored public health intervention strategies that address all lifestyle domains relevant to adolescent health.Scoping review registrationhttps://osf.io/kzu7y/overviewn, DOI: 10.17605/OSF.IO/KZU7Y.